An Examination of WHOOP Fitness Band Usage in College Athletics - Victor Romano; Miracle Etim-Andy (CV. FOUNDAE, 2023)
Wearable technology is novice and beneficial in its ability to retrieve real-time data with minimal hindrance to the performance and mobility of its users. WHOOP fitness band captures physiological metrics and turns them into three metrics: Strain, sleep, and recovery. These metrics allow for personalized monitoring of training metrics to help guide workload. WHOOP bands were distributed to 56 Division II collegiate athletes participating in three sports: Softball (15), women's Lacrosse (15), and Baseball (25). Women's Lacrosse indicated a negative correlation between the hours of sleep players received the day before a game and their respiratory rate during their game (r = -0.55) and a positive correlation between the hours of exercise the day before a game and the respiratory between hours of sleep the day before and respiratory rate the day of the game (r = -0.46) and a moderate negative correlation between hours of exercise the day before a game and the respiratory rate the day of the game (r = -0.55). Baseball indicated a negative correlation between sleep quality the night before the game and duration of exercise the day of the game (r = -0.61). Our examination of performance metrics for three Division II athletic teams using WHOOP fitness straps found that variables differed between teams. Coaches can use WHOOP fitness bands to assist in training and recovering by monitoring pre-game training load, intensity, and sleep.